Two spatial scales in a bleaching event: Corals from the mildest and the most extreme thermal environments escape mortality. (28th July 2013) - Pineda, Jesús; Starczak, Victoria; Tarrant, Ann; Blythe, Jonathan; Davis, Kristen; Farrar, Tom; Berumen, Michael; da Silva, José C. B.
Abstract : In summer 2010, a bleaching event decimated the abundant reef flat coral Stylophora pistillata in some areas of the central Red Sea, where a series of coral reefs 100–300 m wide by several kilometers long extends from the coastline to about 20 km offshore. Mortality of corals along the exposed and protected sides of inner (inshore) and mid and outer (offshore) reefs and in situ and satellite sea surface temperatures (SSTs) revealed that the variability in the mortality event corresponded to two spatial scales of temperature variability: 300 m across the reef flat and 20 km across a series of reefs. However, the relationship between coral mortality and habitat thermal severity was opposite at the two scales. SSTs in summer 2010 were similar or increased modestly (0.5°C) in the outer and mid reefs relative to 2009. In the inner reef, 2010 temperatures were 1.4°C above the 2009 seasonal maximum for several weeks. We detected little or no coral mortality in mid and outer reefs. In the inner reef, mortality depended on exposure. Within the inner reef, mortality was modest on the protected (shoreward) side, the most severe thermal environment, with highest overall mean and maximum temperatures. In contrast, acute mortality was observed in the exposed (seaward) side, where temperature fluctuations and upper water temperature values were relatively less extreme. Refuges to thermally induced coral bleaching may include sites where extreme, high‐frequency thermal variability may select for coral holobionts preadapted to, and physiologically condition corals to withstand, regional increases in water temperature.